Sky's the limit: The operations, renovations and implications of a Montréal gay bar - Allan, James (Université McGill, 1997)
Sky, un Hméga-club" en plein essor situé au coeur du village gai de Montréal, représente plusieurs tendances au sein des clubs et des villages gais de l'Amérique du Nord à la fin du XXième siècle. Ce projet aborde les opérations quotidiennes du Sky, en tenant compte de son architecture complexe, de ses pratiques de gestion, et de sa popularité à l'intérieur du village ainsi que des ramifications théoriques de cet établissement pour la communauté gaie et pour la culture des clubs de nuit en général. Au plan théorique, ce complexe récréatif présentement en expansion constitue un phénomène ni complètement opprimant, ni entièrement libérateur. Bien que le Sky offre certains des avantages d'un "méga-club" pour la communauté gaie--plus grande diversité, accessibilité, et communauté--il possède également les désavantages de ces établissements: la concentration du pouvoir économique, une moins grande présence gaie dans les rues, et la promotion de certaines identités et cultures gaies plutôt que d'autres.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; communication; discipline; environnement; espace sécuritaire; identités LGBTQIA2+; montréal; mémoires/thèses; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; travail

Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

Les usages de la sexualité chez Foucault - PROBYN, Elspeth (Sociologie et sociétés, 1997)
Cet article expose de façon schématique comment certains aspects de la pensée de Foucault dépassent les deux pôles qui ont défini la plupart des débats dans le champ des études gaies et lesbiennes à propos de la sexualité
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques